Associação do polimorfismo no gene da enzima Catecol-O-Metiltransferase (COMT) com expressão de receptores de estrógeno e variáveis clinicopatológicas de cadelas com neoplasias mamárias - Magalhães, Larissa Fernandes (2018)
Catechol-O-methyltransferase (COMT) is an enzyme that acts in the inactivation of estrogen metabolites, which are potentially carcinogenic. The gene polymorphism that codifies this enzyme influences in its activity capacity. The estrogen receptor status of the bitch may be a determining factor in the influence of the COMT genotype in the result of mammary neoplasia. Thus, the aim of the present study was to evaluate the correlation between the the polymorphism of the COMT genotype and the status of the estrogen receptor, besides verifying the relation of the enzyme polymorphism with clinicopathological variables. A total of 59 bitches were used, of which 51 had mammary neoplasms (EG) and eight had no mammary neoplasia (CG). The enzyme polymorphism was evaluated through PCR-RFLP and the estrogen receptors (RE-α) through immunohistochemistry (IHQ). In IHQ, 19,6% and 87,5% of the tumors expressed estrogen receptor in EG and CG, respectively. PCR was performed in 42 animals. Seventeen dogs (47,2%) from EG and only one from CG (16,6%) presented polymorphism (GA genotype). There was no correlation between polymorphism and clinopathological variables, as well as between REα expression and enzyme polymorphism (p = 0.148) in univariate analysis. However, there was correlation of the polymorphism with the occurrence of negative estrogen receptor carcinoma in the multiple regression analysis. Therefore, the conclusion was that female dogs with polymorphism of the COMT enzyme develop more frequently estrogen negative receptor mammary carcinoma.